A partial proteome reference map of Tetragenococcus halophilus and comparative proteomic and physiological analysis under salt stress. Issue 21 (23rd February 2017) - He, Guiqiang; Deng, Jingcheng; Wu, Chongde; Huang, Jun
Abstract : Tetragenococcus halophilus, a moderately halophilic Gram-positive lactic acid bacteria, was widely existed in many food fermentation systems, where salt stress is an environmental condition commonly encountered. Abstract : Tetragenococcus halophilus, a moderately halophilic Gram-positive lactic acid bacteria, was widely existed in many food fermentation systems, where salt stress is an environmental condition commonly encountered. In this study, a partial proteome reference map of T. halophilus was established by using the proteomics approach. A total of 120 proteins were identified and the cluster of orthologous groups (COG), codon adaptation index (CAI), and GRAVY value analyses of the identified proteins were performed. To better understand the salt tolerance mechanisms and stress responses, we carried out a comparative proteomic and physiological study of T. halophilus during salt stress. Comparative proteomic analysis revealed 26 differentially expressed proteins that are mainly involved in cellular metabolism, energy production, stress response, and others. Analysis of the cytoplasmic membrane fatty acids showed that higher proportions of unsaturated fatty acid and higher mean chain length were observed in the cells challenged by salt stress. In addition, the salt shocked cells exhibited higher amounts of intracellular proline, glycine betaine, and trehalose compared with those without salt stress. Results presented in this study may further elucidate the mechanisms of T. halophilus underlying salt stress.